ANALIZA KORELACIJE I KOEFICIJENATA PUTANJA KOMPONENTI PRINOSA SUVE TEŽINE U OBIČNOM SAINFOIN (ONOBRICHIS VICIIFOLIA SCOP.): CORRELATION AND PATH COEFFICIENT ANALYSES OF THE COMMON SAINFOIN - Sabaghnia, Naser (Journal of Agricultural Sciences (Belgrade), 2023)
Sainfoin (Onobrychis viciifolia Scop.) is a perennial forage crop that has received interest in due to its desirable forage properties which is adapted to the temperate climate of the world. The purpose of this investigation was to study phenotypic correlation coefficients between dry forage yield and some morphological traits, and to identify the direct and indirect effects of the associated traits. Thus, 32 ecotypes (landraces) were assessed in the randomized complete blocks design layout with four replications. Positive and statistically significant correlations were determined between dry weight total (DWT) and all of the measured traits except for internode length (IL). To reliable identification the path coefficients, two multicollinearity statistics, tolerance and variance inflation factor (VIF), were considered and two traits (number of nodes per main stem and number of internodes per main stem) were removed from analysis. Path coefficient analyses indicated that number of leaflets per leaf (NLL), height of the longest stem (HLS), and dry weight / fresh weight ratio (DFR) were influenced DWT as first-order traits. Five traits as secondary or tertiary traits affected DWT as number of stems per area (NPA), number of stems per plant (NSP), number of leaves per stem (LS), length of inflorescence (LI) and stem weight / leaf weight ratio (SLR). The importance of main stem properties like length or height, number of leaves, and number of leaflets can be seen for selection, in breeding programs, with the goal of improved common sainfoin forage yield under semi-arid conditions.